2017
DOI: 10.3892/etm.2017.4717
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative benefits of dexmedetomidine combined with flurbiprofen axetil after thyroid surgery

Abstract: The present study determined the effect of dexmedetomidine (Dex) combined with flurbiprofen axetil (FA) on analgesia, immune response, and preservation of cognitive function in patients subjected to general anesthesia. We recruited 100 patients with thyroid surgery and randomly divided them into four groups: Dex (D), FA (F), Dex combined with FA (DF), and saline control (C). The extubation and recovery times for Groups D and DF were significantly longer than for Groups F and C. After extubation, the heart rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
1
13
2
Order By: Relevance
“…Afterwards, flurbiprofen allows analgesia by inhibiting prostaglandin synthesis. 13 In this study, both T2 MAP and HR of the study group were higher than those of the control group (P<0.05), but there was no significant difference in MAP and HR between the two groups at other time periods (P>0.05). The results showed that the anesthetic drugs used in the two groups had little effect on the vital signs of the patients, but when the patients underwent microwave ablation, they were still affected, and the vital signs changed, while the remaining time was short and the vital signs of the patients in the two groups did not change.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Afterwards, flurbiprofen allows analgesia by inhibiting prostaglandin synthesis. 13 In this study, both T2 MAP and HR of the study group were higher than those of the control group (P<0.05), but there was no significant difference in MAP and HR between the two groups at other time periods (P>0.05). The results showed that the anesthetic drugs used in the two groups had little effect on the vital signs of the patients, but when the patients underwent microwave ablation, they were still affected, and the vital signs changed, while the remaining time was short and the vital signs of the patients in the two groups did not change.…”
Section: Discussioncontrasting
confidence: 50%
“… 3 As a non-steroidal targeting analgesic agent, flurbiprofen axetil is generally used after surgery, but its combinations with other drugs before surgery have seldom been reported. 4 This study was to assess the anesthetic effects of flurbiprofen axetil combined with propofol on patients with liver cancer receiving microwave ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Two trials 13,17 recorded the expression of B cells at T1, with 70 patients in the control group and 70 patients in the DEX group.…”
Section: B Cellsmentioning
confidence: 99%
“…Previous studies have suggested that intraoperative dexmedetomidine is associated with significant reductions proinflammatory cytokines and significant stress alleviating (cortisol reducing) properties. [31,33] Both the effects can be more beneficial in the elderly. Whether these results suggest that dexmedetomidine is more effective in elderly patients is subject to further investigations with larger datasets.…”
Section: Discussionmentioning
confidence: 99%